Use sensitivity analysis in evaluating projects Investment under the conditions of risk and uncertainty Case study of glass bottles project in Anbar province - بتال احمد حسين; الراوي محمد مزعل (Journal of Economics and Administrative Sciences, 2009)
This paper studies the investment project evaluation under the condition of uncertainty. Evaluation of investment project under risk and uncertainty is possible to be carried out through application of various methods and techniques. The best known methods are : Risk-adjusted discount rate , certainty equivalent method , Sensitivity analysis and Simulation method The objective of this study is using the sensitivity analysis in evaluation Glass Bottles project in Anbar province under the condition of risk and uncertainty. After applying sensitivity analysis we found that the glass bottles project sensitive to the following factors (cash flow, the cost of investment, and the productive age), which requires attention to these factors, especially cash flow and cost of investment. If cost of investment has increased by more than 41% project has negative present value, also if the cash flow dropped by more than 31% the project will achieve a negative present value .